1989
DOI: 10.2754/avb198958020245
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Cows after Dystocias and Complicated Puerperium with Respect to Bacteriological and Mycological Findings in the Genitalia

Abstract: Seventy-three cows with the history of laboured calving and complicated puerperium were observed for persisting pathological conditions in the genitalia, the incidence of bacteria and micromycetes in the cervical mucus and for subsequent fertility. Clinical examination at 28 to 32 days after parturition revealed persisting pathological processes, mainly inflammations, in the genitalia of 75.34 %, incomplete involution of the uterus in 50.68 %, absence of the sexual cycle in 26.02 % and the incipient syndrome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Vlcek et al found increase of the insemination interval, service-period and insemination index in cows that yielded pathogenic and potentially pathogenic micromycetes. 15 No significant difference between cows with positive and negative fungal cultures in the first and second examinations (P>0.05) con-firmed that the immune system did not respond to the exposure of uterus to fungi. This issue is reported for the first time and to the best of the researchers' knowledge there have been no reports regarding this subject.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vlcek et al found increase of the insemination interval, service-period and insemination index in cows that yielded pathogenic and potentially pathogenic micromycetes. 15 No significant difference between cows with positive and negative fungal cultures in the first and second examinations (P>0.05) con-firmed that the immune system did not respond to the exposure of uterus to fungi. This issue is reported for the first time and to the best of the researchers' knowledge there have been no reports regarding this subject.…”
Section: Discussionmentioning
confidence: 92%
“…were the highest isolated fungi from vaginal mucus of cows with complicated puerperium. 15 In another survey, Penicillium spp. and Candida albicans were the most common isolated fungi.…”
Section: Discussionmentioning
confidence: 98%
“…(2015) reported that microbiological cultures from reproductive tract of repeat breeder dairy heifers did not show any fungal growth. Vlcek et al . (1989) found pathogenic and potentially pathogenic fungi to be 22% and 17% cows, at first and second months after parturition, respectively.…”
Section: Introductionmentioning
confidence: 99%